Improving Acoustic Properties of Sandwich Structures Using Recycled Membrane and HoneyComb Composite (RMHCC) - Giuseppe Ciaburro; Virginia Puyana Romero; Gino Iannace; Luis Bravo Moncayo (Buildings, 2024)
The motivation behind this study is to improve acoustic environments in living spaces using sustainable materials. This research addresses the challenge of enhancing the acoustic properties of sandwich structures through the integration of a honeycomb core with a membrane made from recycled materials, forming a recycled membrane honeycomb composite (RMHCC). The main objective is to develop a novel sandwich material with sound-absorbing characteristics suitable for real-world applications. The study employs both experimental methods and simulations, where a conventional hexagonal honeycomb geometry is combined with the recycled membrane to form the composite structure. A simulation model was developed to evaluate the effectiveness of the metamaterial in reducing reverberation time within a church setting. The results indicate that the RMHCC shows significant potential in improving acoustic performance, with a notable reduction in reverberation time even with minimal usage, highlighting its suitability for enhancing acoustic environments in various applications.